The leadership development model influencing drug prevention management and performance of schools under the local administrative organization - Phuttanu, Vivat; Cain, Parisha Marie; Kaewhanam, Kathanyoo; Kaewhanam, Phimlikid (Asian Journal of Education and Training, 2024)
This study employs a mixed-methods approach, combining quantitative and qualitative research methodologies to investigate the dynamics of leadership, management, and performance in the context of drug prevention within schools under local administrative organizations. The research pursues three main objectives: (1) to examine the key elements of leadership, management, and performance related to drug prevention in these educational institutions, (2) to analyze the direct, indirect, and combined influences of leadership on the management and performance of drug prevention efforts, and (3) to formulate policy recommendations for influential leadership development models tailored to enhance the management and performance of drug prevention initiatives. Quantitative data were collected from 400 personnel within educational institutes under the Sisaket Local Administrative Organization, utilizing stratified random sampling and a questionnaire with a high-reliability score of 0.978. Concurrently, qualitative insights were from 12 purposively selected educational institutes in the same administrative context through the focused group. The analytical toolkit included frequency, percentage, mean, standard deviation, structural equation analysis, and content analysis. Key findings indicate the appropriateness of utilizing trait-based, behavior-based, and situational leadership alongside Principles of management to construct a comprehensive structural equation model. The performance emerges as primarily influenced by Principles of management, all statistically significant at 0.01 level. In terms of policy suggestions, the focus centers on fostering a knowledgeable and collaborative team, developing leadership skills through cooperation, and creating an organizational culture that supports learning and development. This integrated leadership development approach is the picture to significantly impact the effective management and prevention of drug abuse in schools under local administrative organizations.